THE CHARACTERISTICS OF SUICIDAL AND NON-SUICIDAL SELF-INJURIOUS BEHAVIORS IN CHILDREN AND ADOLESCENTS - Vardanyan, Kamo (Modern Psychology, 2022)
The ongoing wars in different countries, post-war crises, the lack of a clear state policy in the field of suicide prevention, unfavourable socio-economic processes, and the growing number of various human diseases are just a few reasons for the extreme form of self-destructive behaviour of a person, which is called suicide in science. A modern person is forced to constantly be exposed to various frustrating and stressful influences, which make a person face the need to show appropriate adaptive behaviour. People whose psychological defence mechanisms are weaker or have been under psycho-traumatic influences for too long, as such “adaptive” behaviour, often choose mild forms of auto-aggressions. In this context, suicides and suicide attempts among children and adolescents are the most sensitive issues.In science, if there is a relatively sufficient amount of research on adult suicides, suicides of children and adolescents have not been studied systematically and comprehensively. Therefore, there are still many gaps and problems in this field.For this purpose, we studied 48 criminal cases related to children’s and teenagers’ suicide, and respectively, a number of materials have been submitted to forensic psychological examination, alongside research from renowned foreign experts and published scientific papers.The research has been carried out using retrospective analysis, retrospective autopsy, expert interview, content-based and other necessary methods, and analysis of specialised professional literature.The given article touches upon the manifestations of child and adolescent self-destructive behavior.It’s typical of child suicide that before a child commits suicide, he or she doesn’t perceive the death irreversibility; as a result the conscious fear of death is missingwhich leads to unpremeditated, tactile and impulsive suicide.In the pre-suicide stagethe suicidal tendency movement is missing: from suicidal ideation to suicidal decision, typology of the meaning of suicide and its factors.“The destructive tendency” underlies the adolescent suicide which increases the likelihood of them turning to suicide, shortens the duration of the pre-suicidal state, and even increases the probability of counter-suicidal actions under the impact of stressors and frustraters.In order to prevent suicide, it’s proposed to create a scientific center for the study of auto-destructive behavior, whose activities should be aimed at conducting scientific studies of the phenomenon, ensuring the development of the existing scientific potential in the area and its effective use, publication of self-destruction and suicide-related monographs, books, guidelines and manuals, constantprocess monitoring, activities towards diagnosis and rehabilitation of suicidal tendencies, research and localization of international experience in this area.
Keywords: self-destructive behavior,; destructive behavior,; destructive tendency; suicide,; suicide attempt,; adolescent suicide.